Bilingual and multilingual medium of instruction policy: A panacea for creating an Inclusive learning environment in Nigeria (2024)
This paper examines the potential of bilingual and multilingual medium of instruction (MOI) policy as a solution for creating an inclusive learning environment in Nigeria. With over 250 ethnic languages and a complex linguistic diversity, Nigeria's education system faces significant challenges in providing equal access to quality education for all students. The dominant use of English as the sole MOI has resulted in a linguistic barrier, marginalizing mother-tongue speakers and perpetuating educational inequalities. This research argues that a well-implemented bilingual and multilingual MOI policy can address these challenges by promoting linguistic diversity and inclusivity, enhancing academic achievement and cognitive development, fostering cultural preservation and identity, bridging the gap between home and school languages, empowering marginalized communities through a critical analysis of existing literature, policy documents, and stakeholder interviews, this study explores the benefits, challenges, and implementation strategies of bilingual and multilingual MOI policy in Nigeria. The findings highlight the need for a contextualized and flexible approach, taking into account regional language dynamics, teacher training, and resource allocation. This research contributes to the ongoing debate on language policy and education in Nigeria, providing evidence-based recommendations for policymakers, educators, and stakeholders to create a more inclusive and effective education system. By embracing linguistic diversity, Nigeria can unlock the potential of its diverse student population and foster a more equitable and harmonious society.